The analysis of modifications in cooling systems for high-performance data centers. A case study - Rusowicz, Artur; Ruciński, Adam; Laskowski, Rafał (International Conference “Environmental Engineering”, 2017)
One of main issues concerning server room operation is appropriate cooling of electronic modules to prevent excessive heat generation resulting in their damage. Since high cooling powers are required, precision air conditioning systems are used that are specially designed for cooling server and equipment rooms, server cabinets, etc. These devices require very large energy supplies. The paper proposes an upgrade of a cooling system for three server rooms in which refrigeration equipment with a cooling power of 1.873 MW is installed. The average actual cooling power demand is 890 kW, and some units work as a standby. Thir-eight direct-evaporation air-conditioning cabinets are installed. The refrigerant is R407C. The devices have been operated for 14 years; therefore, the refrigeration equipment should be replaced with modern units. The paper compares three approaches: replacing the units with similar ones based on newer technology, introducing contained aisle configurations of rack cabinets and units based on newer technology with additional EconoPhase modules. The application of free cooling was not analyzed since mounting additional heat exchangers was impossible (due to the lack of space and limited roof loading capacity). The paper provides capital and operating costs of the solutions. The introduction of up-to-date units and replacing condensers resulted in lowering the electric power demand by 16%. The simple payback time (SPBT) of this solution is 18.8 years. The energy savings achieved through the second solution (contained aisle configurations of rack cabinets) amount to 37.8%, with SPBT equal to 8.38 years. Variant III, consisting in using modern units with additional EconoPhase modules, significantly improves energy savings (48.3%) but it requires large capital expenditure, with simple payback time of 12.1 years.
Keywords: data center; air conditioning; infrastructure energy efficiency